Enlightenment Germany and the Invention of Siberia - Michel Espagne (Studia Litterarum)
During the period of German Enlightenment, German scholars at service in the Russian state began scientific exploration of Siberia and organized the “Great northern expedition” (1733–1743) which was later completed by other researchers. Johann Georg Gmelin, Carl Heinrich Merck, Georg Wilhelm Steller, Gerhard Friedrich Müller, and Peter Simon Pallas among others focused on the religious life, languages and everyday life of the Siberian ethnic groups they encountered. Their accounts remained for a long time unpublished as they were a “formal” property of the Russian Academy of Sciences. Not only are they a valuable contribution to the invention of Russian identity conceived as part of the Eurasian space, they also form the basis of new sciences such anthropology and linguistics resulting from the contact between German universities and the widely unexplored Siberian world.